1977
DOI: 10.1080/00288330.1977.9515692
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of sediments in relation to trophic condition of eight Rotorua Lakes

Abstract: Chemical parameters (pH, Eh, carbon, Kjeldahl nitrogen, total phosphorus, 0.5M H 2 SO 4 -extractable phosphorus, organic phosphorus, and water-soluble phosphorus) were measured in the surface layers of sediments collected from various depths in Lakes Rotowhero, Okaro, Ngapouri, Rotokakahi, Okareka, Tikitapu, Okataina, and. Rotoma during October 1972. The sediments of the productive geothermal lake, Rotowhero, were markedly different from those of the cold-water lakes: they had relatively low pH values, high ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 16 publications
1
23
0
Order By: Relevance
“…During the: late 1950s and early 1960s, Jolly (1968) andFish (1969b, 1970 measured oxygen levels at depth in several Rotorua lakes providing, thereby, valuable baselines against which to assess subsequent changes. By comparing dissolved oxygen profiles of seven Rotorua lakes in 1970-71 with earlier data, McColl (1972) showed that oxygen had decreased in at least six of the seven lakes during the previous 15 years and that the decreases were correlated with increased agricultural, forestry, or urban development in the catchments (Fig. 2).…”
Section: Measuring Nutrients and Nutrient Limitationmentioning
confidence: 86%
See 3 more Smart Citations
“…During the: late 1950s and early 1960s, Jolly (1968) andFish (1969b, 1970 measured oxygen levels at depth in several Rotorua lakes providing, thereby, valuable baselines against which to assess subsequent changes. By comparing dissolved oxygen profiles of seven Rotorua lakes in 1970-71 with earlier data, McColl (1972) showed that oxygen had decreased in at least six of the seven lakes during the previous 15 years and that the decreases were correlated with increased agricultural, forestry, or urban development in the catchments (Fig. 2).…”
Section: Measuring Nutrients and Nutrient Limitationmentioning
confidence: 86%
“…The initial approach in the 1970s was to classify New Zealand lakes according to trophic state based on indices of eutrophication that had been developed in the Northern Hemisphere. For example, measurements of chlorophyll a (as an index of phytoplankton biomass), transparency (Secchi depth), various forms of phosphorus and nitrogen, and dissolved oxygen revealed a wide range of trophic states among lakes in the Rotorua area (McColl 1972). This study is notable in being the first to document the relation, in New Zealand, between increased land development 1966-70 1971-75 1976-80 1981-85 3O-i 1966-70 1971-75 1976-80 1981-85 1966-70 1971-75 1976-SO 1981 …”
Section: Eutrophicationmentioning
confidence: 99%
See 2 more Smart Citations
“…The Rotorua lakes vary widely in trophic status (oligotrophic to highly eutrophic) and have two predominant mixing regimes; monomictic and polymictic (Table 1) (McColl, 1977;Burns et al, 1997;Trolle et al, 2008). Lake trophic status and silica availability are important controls on sedimentation rates (mainly diatom frustules where there is sufficient silica) and the extent of chemical reduction within the sediments (Trolle et al, 2008).…”
Section: Study Sitesmentioning
confidence: 99%